THE EARLY RESULTS OF RADICAL SURGERY IN TREATMENT OF RECTAL CANCER (Vietnam Journal of Community Medicine, 2021)
Objectives: To evaluate the early result of radical surgical treatment of rectal carcinoma. Subjects and methods: Longitudinal follow-up study on 109 patients diagnosed with rectal carcinoma who were surgically treated at Department of colorectal and perineal surgery, Viet Duchospital from October 2016 to May 2019. Results: Complications of anastomotic leakage (2.75%). Postoperative bleeding (1.83%). Abdominal wound infection (10.09%). Postoperative enteroplegia (5.50%). Urinary retention (4.59%). Intestinal obstruction (2.75%). Bladder leakage and psychosis both accounted for 1.83%. Intra-abdominal bleeding, pelvic abscess, acute pancreatitis all accounted for 0.92%. Parastomal hernia had a patient,accounting for 0.92%. There were 18.37% of patients relapse after surgery. There were 11.22% of patients with distant metastasis detected after surgery, the metastatic organs were liver and lung metastasises.Conclusion: Complications of radical surgery for rectal cancer were mainly anastomic leakage, wound infection, postoperative enteroplegia. The postoperative recurrence rate was 18.37% in allfollowing (11.22% of patients had distant metastases after surgery).
Keywords: Rectal cancer, early results, radical surgery.